Ungkapan Otsukaresama dalam Obrolan Chat Orang Jepang di Eneos Saijo Inta Service Station Hiroshima - Leo Sadewo (KIRYOKU, 2023)
This study aims to describe the use of the greeting expression otsukaresama in the Japanese Line application chat at Eneos Saijo inta service station Hiroshima. The research uses descriptive methods and qualitative approaches and  also uses viewing and note-taking techniques to process data in the form of message history in Line chats that written directly by Japanese people. Data was collected on message history for the data period from 05 February 2020 to 25 February 2020 in Hiroshima Prefecture. The expression is carried out as an expression of greeting by the speech partner to the speaker. The use of greetings is used as an expression of saying good bye, announcing information, apologizing, and greetings to speech partners specifically, as well as being used as greetings to fellow employees or friends like from superiors to subordinates and vice versa. based on the time of use of the expression otsukaresama starting from 08:00WJS to 20:00WJS. outside these hours, greetings will use expressions such as ohayou gozaimasu for the expression of greetings in the morning. No use of konnichiwa greetings found in chat messages.